Gulf Cooperation Council strategies to adopt blockchain technology and the possible results of its application -Reading in the UAE experience- (Journal of Economic Additions, 2020)
Blockchain is one of the leading emerging technologies that provide modern business patterns that keep pace with the contemporary requirements of the economy, and there is an increasing trend for countries to use this technology. The aim of the study is to highlight the strategies used to adopt blockchain technology in the UAE as a sample of the leading Arab experiences in this field. One of the most important findings of the study is that the UAE has a strong technological infrastructure that facilitates rapid access to blockchain.In addition to other efforts such as the Global Blockchain Council in 2016 to monitor the process of the transition to blockchain technology, which will work to promote the "Smart Dubai" project and achieve savings of more than 11 billion dirhams, and save time and effort, and reduce carbon emissionsKeywords: Blockchain; Bitcoin; Digital currency; UAE; Smart Dubai.Jel Classification Codes: O31, O33.